Development of co-operation between a research institute and enterprises in the context of marketing communication - Niemczyk, Aleksander (The Institute of Aviation, 2018)
Aim of the article is presentation of results of recent research on the effectiveness of practical solutions used in marketing communication of the Institute of Logistics and Warehousing, leading to development of cooperation with enterprises. Thanks to the management, the appropriate information reaches definite groups of clients through multiple channels. E-marketing of scientific and research organizations is carried out mainly through web sites, web portals, social media. The analytical and research instruments in the marketing of scientific and research organisations used for measuring the effectiveness and efficacy of marketing communication include: Google Analytics, Seo Stat, Salesmanago, Advertising Value Equivalency and a range of reports. Product line and product managers are employees who are highly qualified and often possess unique competences. Ongoing research coupled with direct contact with companies results in a constant improvement in the services rendered and generation of innovative products.